TensioBot: a Chatbot Assistant for Self-Managed in-House Blood Pressure Checking. - Echeazarra, Leyre; Pereira, Juanan; Saracho, Ramón (Journal of Medical Systems, 2021)
Hypertension is a chronic condition that can lead to serious health problems. Patients with High Blood Pressure (HBP) are often asked to have their BP checked at home. The traditional at-home procedure has some drawbacks, such as forgetting to check or write down the values, errors in transcribing the numbers, or the impossibility of immediately notifying medical staff of out-of-range BP values. To facilitate self-measurements by patients at home we devised TensioBot, a Telegram based chatbot. The bot sends patients reminders to check their BP, advice on good monitoring practices, measurement tracking, medical alerts and allows healthcare professionals to access up-to-date measurement information. TensioBot has been tested for two years in a randomized controlled trial with 112 patients (55 using the bot and 57 in the control group). We found that, although the bot group showed similar results in terms of adherence to the BP checking schedule, bot users scored better in terms of knowledge and skills on BP checking best practices. Participants rated the bot very positively, perceived it as useful and easy to use, and continued to use it after the intervention. Moreover, all data being equal, we describe some other benefits of using a chatbot for self-managed in-house BP control, both for patients and healthcare professionals and systems.